Perbandingan Perhitungan Harga Pokok Produksi Berdasarkan Metode Full Costing Vs Variable Costing Pada Produksi Sambel Pecel - Darno Darno; Liana Dwi Muasyaroh (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
Manufacturing company is a company that processes raw goods into semifinished or finished goods. In manufacturing companies to determine the selling price does not escape from the calculation of the cost of production which is appropriate and in accordance with cost accounting standards. PT. Indramukti Segara is a fast food company that comes from natural ingredients. Products produced by PT. Indramukti Segara includes: pecel sauce and fried onions. Calculation of cost of goods manufactured by PT. Indramukti Segara is not right to determine the selling price, because the company only calculates the material used multiplied by the price of the material. On this occasion the author analyzes the cost of production in accordance with the Cost Accounting standard and conducts a comparison between two methods, namely: the full costing method and the variable costing method.  The purpose of this study is to compare the cost of production using the full cost and variable costs method. The data collected comes from the results of interviews with the Production Administration, Sambel Pecel production supervisor, and employees of Sambel production at PT. Indramukti Segara. Data obtained includes data on raw material expenditure, direct labor costs, and factory overhead costs that are fixed and variable. Based on the comparison of the calculation of Cost of Production between the full cost method and variable costs there are differences, because the full cost method calculates all costs that are fixed and variable while the variable cost method only calculates costs that are variable in nature.